PAKAIAN MUSLIMAH DALAM PERSPEKTIF HADIS DAN HUKUM ISLAM - Maidatus Sa'diyah; Muhammad Abror Rosyidin (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
Regardless of whether they follow the rules of Islam or the rules of general society, strong-minded and sensible people desire to look attractive. Indonesian people, whose majority population is Muslim, must know how to dress appropriately according to their beliefs. However, recently many Muslim women have been found not dressing in accordance with Islamic laws and teachings. Muslim women who are accustomed to following Islamic dress norms that are ingrained in society and are accustomed to dressing according to sharia law need to be taught good dress practices from a young age. The main purpose of this article is educate readers regarding Muslim women's clothing procedures in accordance with Sharia. This study shows that, in summary, by using the perspective of the Prophet's hadith.